Microlattices with tailored properties as thermoplastic composite sandwich cores - Vos, C.J. de; Bal D.B.M.; Pragt, I.J.; Wits, W.W.; Veul, R.P.G. (My University, 2025)
Carbon microlattices demonstrate potential as substitutes for traditional honeycomb cores in aerospace applications due to their exceptional combination of ultra-low weight, high compression strength and stiffness. Integrating them into thermoplastic composite structures could be one of their first industrial applications. This study demonstrates that composites with carbon core materials can be realised and that carbon microlattices can be produced at a larger scale using commercially available stereolithography and sintering equipment.